High-power characterization of a microcutter actuated by PMN-PT piezocrystals - Kuang, Yang (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2015)
An ultrasonic microcutter is an alternative approach to conventional ultrasonic instruments actuated by sandwich piezoelectric transducers for surgery. This paper reports high-power behavior of a microcutter actuated by the piezocrystal lead magnesium niobate-lead titanate (PMN-PT), defining its practical performance and the feasibility of PMNPT actuation for surgical applications. The microcutter was driven at resonance with constant current amplitudes, either unloaded or loaded by poultry breast tissue, until its behavior achieved a steady state. During this driving process, its electric impedance, resonant frequency, and vibration velocity, along with the temperature increase of the PMN-PT, were recorded in real time. The microcutter produced a maximum vibration velocity >2.8 m/s with an excitation current of 0.11 A(rms). The mechanical loss increased significantly with current amplitude, resulting in a maximum temperature increase approaching 50°C around the interface between the PMN-PT and the blade, where they were bonded together with epoxy. Because of the low phase-transition temperature of PMN-PT, this temperature rise prevented the microcutter from working at higher current amplitudes. Along with the high vibration velocity, it also caused a frequency shift downward by 3 kHz at the same current amplitude. During tests with poultry breast tissue, radiation reactance increased the resonant frequency and the radiation resistance increased the loss of the microcutter. However, the loss did not further increase the temperature of the piezoelectric material. The maximum force and the overall work required to penetrate the microcutter into poultry breast tissue were reduced by 47.1 ± 8% and 53.5 ± 6%, respectively, when the microcutter was actuated at a current of 0.07 A(rms)